Intangible resources and competetive position of Polish credit unions - Rajchelt-Zublewicz, Magdalena (Zasoby niematerialne a pozycja konkurencyjna Polskich Unii Kredytowych, 2018)
Polish credit unions have been operating on the Polish financial market for nearly twenty five years and have been providing services to nearly two million of their members, which may be an indicative of their competitiveness. The analysis of their situation points out that the market is heterogeneous and diversed by the unions’ size, number of members as well as the quality of their resources. Due to the fact that environmental factors for most Polish credit unions are similar, it is necessary to search for reasons of differences in the achieved competitive position within these organizations. In this context, the question arises about the factors that cause some credit unions to achieve significantly better competitive positions than others. A literature review suggests that the intangible resources might have an influence on the achieved competitiveness. The purpose of this paper is to empirically verify the relationship between intangible assets and the competitive position achieved by Polish credit unions. The author conducted a study in which she examined whether the intangible resources of credit unions could differentiate them in terms of achieved competitive position. The article is a presentation of the results of research in this area
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 538, s. 376-389
Keywords: intangible resources; competitive position; Polish credit unions; zasoby niematerialne; pozycja konkurencyjna; polskie unie kredytowe